Pengaruh Faktor Fundamental Terhadap Harga Saham Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2020 - Putu Eka Nopiyani (ARTHA SATYA DHARMA, 2022)
This research aims to analyze and test the effect of fundamental factors projected by Current Ratio (CR), Debt to Equity Ratio (DER), Return On Asset (ROA), and Earning Per Share (EPS) on the share price of pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the period 2015-2020. This research used secondary data in the form of company financial statements with a total of 30 research samples. Sampling techniques use purposive sampling with criteria. The research data in the test used the Eviews 9.0 program with panel data regression analysis methods. The results showed that the variable Debt to Equity Ratio (X2) partially significant effect on the share price of pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the period 2015-2020. While The Variabel Current Ratio (X1), Return On Asset (X3), , Earnings Per Share (X4) partially no effect on the share price of pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the period 2015-2020.